(untitled) (Revista Sistemas de Producción Agroecológicos, 2016)
The agroecology is a discipline that provides the scientific and methodological basis for study, manage and evaluate agro-ecosystems in a holistic way, which it has emerged as a valid technological option for the management of natural resources since, among other things, incorporates collective social actions of a participatory nature, enabling the design of sustainable farming systems as a pillar of development that points to the foundation of ecological and social crisis of peasant and industrial-capitalist production in the region. In that sense, the agroecology not only focuses on crops and animals but on ecological sustainability, socioeconomic and cultural of production system. Addition to supplying a scientific basis for achieving sustainable productivity, the agroecology emphasizes the ability of local communities to innovate, evaluate, and adapt to extreme heterogeneous conditions, through participatory research methods and farmer-to-farmer extension. The agroecological technologies emphasize in the diversity, synergy, recycling and integration, and in the social processes that value community involvement, which is the key human resource, as the cornerstone of any strategy aimed at increasing the options involving rural population, especially farmers with scarce resources. The approach farmer to farmer is precisely, one aspect of relevance to consider in the proposal of agroecological thought, attending of course to the inclusion of technical professionals as facilitators of the process, who in principle should understand the complexity of the agricultural system and its anthropological, social, economic, political and ecosystems relationships, In conclusion, the agroecological designs are unique in the local context and has its peculiarities from each dimension of sustainability including aspects considered as: Cultural, ecological, political, productive and economic, among others; in this way, it define that agroecological designs are built from the analysis of context and existing specific needs by producers (sociocultural) who are responsible and direct mourners of agricultural processes in each region.